(untitled) (Research, Society and Development, 2020)
In the current globalization scenario, the concept of agribusiness is increasingly present among organizations, establishing the sector to move forward in the search for strategic competition alliances, such as the implementation of certification. Thus, the establishment of ISO certification has become a distinguishing feature, as it guarantees a concept of greater acceptability and market vision, as it proves that the processes and products followed a rigorous standardization process. Based on this scope, this work aimed at building a descriptive survey around the certifications of international standards, with emphasis on ISO’s 9001 (Quality Management) and 14001 (Environmental Management), focused on the agribusiness. The data referring to the ISO 9001 and ISO 14001 certifications were collected in the existing database of the International Organization for Standardization - ISO, and analyzed for the historical period between the years 1993 and 2017, and subdivided between large regions in comparison with the evolution of the number of certification registrations carried out by Brazilian companies, during the same period. For analysis, the sectors of economic activities related to agribusiness were selected, totaling 6 sectors classified according to the IAF. The total number of certifications 90001 and 14001, have shown to be increasing over the years, which reports a continuous search for improvements in the management process of companies, where Brazil stands out as a highlight in the scenario of central and south america, to the total number of certifications aimed at agribusiness, acting as an agro-exporting country.